Whence 'zoster'? The convoluted classical origins of a sometimes illogical term. Issue 1 (12th August 2016) - Schott, G D
Abstract : The term 'zoster' is nowadays associated with 'herpes zoster', the condition resulting from reactivation of the latent varicella-zoster virus which causes shingles. But in antiquity the meaning of 'zoster', a Latin word originating from the Greek for a belt or girdle, was variously associated in men with a form of body armour which could enclose just one half of the body; in women with a garment worn around the waist and sometimes called a 'zona'; and with a place, Zoster, linked mythologically then with the goddess Leto and her zona. Around 48 AD, the Roman physician Scribonius Largus became the first to associate 'zona' with 'herpes', and to attribute a medical meaning to 'zona', here an abbreviation of 'zona ignea' ('fiery girdle'). Although in the past the terms 'zoster' and 'zona' were sometimes used interchangeably, today only 'zoster' remains—even when etymologically illogical in those patients whose zoster rash occurs in body areas other than the trunk.